Dynamic Calculation of the Youth Bridge Over the Danube River in Bratislava - Melcer, J. (Engineering Transactions, 1995)
The new bridge was built over the Danube river in Bratislava. Prior to opening of the bridge, its dynamic calculations were clone according to the Czecho-Slovak Standard. The natural frequencies and modes of free vibration were calculated. The calculations were clone in several variants using the finite element method. As a control method, the so-called Kolousek’s slope deflection method was used. In the next step, the values of the dynamic coefficients were numerically simulated. The dynamic coefficients were determined from the bridge response produced by simultaneous runs of two vehicles arranged in one row, as they crossed the bridge. All numerically obtained results were tested by experimental measurements of the structure.